Health effects of nutrients and environmental pollutants in Baltic herring and salmon: a quantitative benefit-risk assessment - Jouni T. Tuomisto; Arja Asikainen; Päivi Meriläinen; Päivi Haapasaari (BMC, 2020)
Abstract Background Health risks linked with dioxin in fish remain a complex policy issue. Fatty Baltic fish contain persistent pollutants, but they are otherwise healthy food. We studied the health benefits and risks associated with Baltic herring and salmon in four countries to identify critical uncertainties and to facilitate an evidence-based discussion. Methods We performed an online survey investigating consumers' fish consumption and its motivation in Denmark, Estonia, Finland, and Sweden. Dioxin and methylmercury concentrations were estimated based on Finnish studies. Exposure-response functions for several health endpoints were evaluated and quantified based on the scientific literature. We also quantified the infertility risk of men based on a recent European risk assessment estimating childhood dioxin exposure and its effect on sperm concentration later in life. Results Baltic herring and salmon contain omega-3 fatty acids and vitamin D, and the beneficial impact of these fishes on cardiovascular diseases, mortality, and the risk of depression and cancer clearly outweighs risks of dioxins and methylmercury in people older than 45 years of age and in young men. Young women may expose their children to pollutants during pregnancy and breast feeding. This study suggests that even in this critical subgroup, the risks are small and the health benefits are greater than or at least similar to the health risks. Value of information analysis demonstrated that the remaining scientific uncertainties are not large. In contrast, there are several critical uncertainties that are inherently value judgements, such as whether exceeding the tolerable weekly intake is an adverse outcome as such; and whether or not subgroup-specific restrictions are problematic. Conclusions The potential health risks attributable to dioxins in Baltic fish have more than halved in the past 10 years. The new risk assessment issued by the European Food Safety Authority clearly increases the fraction of the population exceeding the tolerable dioxin intake, but nonetheless, quantitative estimates of net health impacts change only marginally. Increased use of small herring (which have less pollutants) is a no-regret option. A more relevant value-based policy discussion rather than research is needed to clarify official recommendations related to dioxins in fish.